"O Mur Apunar Desh": Embodying Unity in Diversity Through Assam's Cultural Anthem - Pallathadka, Harikumar; Roy, Parag Deb; Sarkar, Rita (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This research examines the profound cultural significance of "O Mur Apunar Desh" (O My Beloved Land), Assam's state anthem, as a powerful symbol of unity within India's diverse cultural landscape. Written by literary luminary Lakshminath Bezbarua and composed by Kamala Prasad Agarwala in 1909, this anthem transcends its regional origins to represent the harmonious coexistence that characterizes India's national identity. Through rigorous historical analysis, ethnomusicological exploration, and examination of contemporary socio-cultural contexts, this study demonstrates how "O Mur Apunar Desh" serves as a compelling exemplar of cultural expressions that foster national integration while preserving distinctive regional identities. The paper employs interdisciplinary methodologies including textual analysis, ethnographic observation, and historical contextualization to illuminate how this anthem continues to resonate across generations, serving as both a repository of collective memory and a living bridge between Assam's particular cultural heritage and India's broader national narrative.